Diagnostika in zdravljenje akutne zastrupitve - Možina, Martin (Medicinski razgledi, 2009)
In addition to well known toxic plants and animals, rapid development in the last decades has produced millions of new molecules, toxic chemicals, drugs and potentially toxic products, which can give rise to poisoning cases. Acute poisonings take an important place in emergency rooms, whether by their prevalence or by their varied etiology and clinical presentation. The basic principles of the diagnostics and treatment of poisoning are similar to those in other diseases, but they have certain specific characteristics. The fate ofa poisoned victim is determined by the use of adequate measures in the firstfew minutes or hours after exposure to the poison. Therefore, all measures must be quick, correct and performed in a proper sequence. Doctors who are treating patients with acute poisoning must be familiar with the most common poisons and the type of poisoning they cause, as well as with specific emergency procedures, including the methods for primary poison elimination andthe use of emergency antidotes.
Keywords: Poisoning; Zastrupitev; Urgentna stanja; Diagnosis; Anamneza; Therapy; Fizikalna preiskava; Medical History Taking; Akutna bolezen; Physical Examination; zastrupitve; Emergencies; Acute Disease; toksikologija; zdravljenje; diagnostika; nujna stanja